Pragmatics in the Use of Social Media Language: A Case Study of Teenagers - Juliana, Eva (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This research examines the pragmatic aspects of language use on social media by teenagers, focusing on how they convey meaning and intent through online messages. The main aim of this study is to understand the patterns of pragmatic language use and the factors influencing the choice of communication strategies among teenagers on social media. The methodology employed is a literature review with qualitative analysis of various previous studies discussing pragmatics, adolescent communication, and social media. The findings indicate that teenagers tend to employ pragmatic strategies such as irony, sarcasm, and indirect markers to deliver messages effectively and maintain social relationships. The use of these strategies is influenced by cultural factors, social context, and the closeness of relationships between users. These results underscore the importance of understanding pragmatic aspects when studying teenage communication on social media, as well as its implications for developing digital literacy and effective communication skills. Keywords: Pragmatics, Language, Social Media, Teenagers